Photodynamic Therapy: Highly Biocompatible Carbon Nanodots for Simultaneous Bioimaging and Targeted Photodynamic Therapy In Vitro and In Vivo (Adv. Funct. Mater. 37/2014). (October 2014) - Choi, Yuri; Kim, Seongchan; Choi, Myung‐Ho; Ryoo, Soo‐Ryoon; Park, Jongnam; Min, Dal‐Hee; Kim, Byeong‐Su
<x xml:space="preserve">Abstract</x> On page 5781, targeted delivery of photosensitizer (PS) and therapeutic photodynamic effect are achieved by folic acid (FA) conjugated carbon dot (CD) as a carrier of PS, zinc phthalocyanine (ZnPc). D.‐H. Min, B.‐S. Kim and colleagues demonstrate how the CDs prepared by thermal decomposition of α‐cyclodextrin are biocompatible, highly fluorescent, and water dispersible. The ZnPc‐loaded FA‐conjugated CD shows excellent efficacy as photodynamic therapy to the target cancer cells upon irradiation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>